2023
DOI: 10.2147/tcrm.s410277
|View full text |Cite
|
Sign up to set email alerts
|

Current and Novel Therapeutics for Articular Cartilage Repair and Regeneration

Abstract: Articular cartilage repair is a sophisticated process that has is being recently investigated. There are several different approaches that are currently reported to promote cartilage repair, like cell-based therapies, biologics, and physical therapy. Cell-based therapies involve the using stem cells or chondrocytes, which make up cartilage, to promote the growth of new cartilage. Biologics, like growth factors, are also being applied to enhance cartilage repair. Physical therapy, like exercise and weight-beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 166 publications
0
8
0
Order By: Relevance
“…In articular cartilage, a large number of growth factors cooperate to regulate the homeostasis of articular cartilage [ 36 ]. Most studied and tested for clinical use are transforming growth factor‐β1, bone morphogenetic protein‐2, bone morphogenetic protein‐7, IGF‐1, fibroblast growth factor‐2, fibroblast growth factor‐18 and platelet‐derived growth factor [ 26 , 91 ]. Multiple growth factor/cytokine modulation therapies are currently undergoing clinical trial investigations but then only for OA.…”
Section: Treatment Choicesmentioning
confidence: 99%
“…In articular cartilage, a large number of growth factors cooperate to regulate the homeostasis of articular cartilage [ 36 ]. Most studied and tested for clinical use are transforming growth factor‐β1, bone morphogenetic protein‐2, bone morphogenetic protein‐7, IGF‐1, fibroblast growth factor‐2, fibroblast growth factor‐18 and platelet‐derived growth factor [ 26 , 91 ]. Multiple growth factor/cytokine modulation therapies are currently undergoing clinical trial investigations but then only for OA.…”
Section: Treatment Choicesmentioning
confidence: 99%
“… 21 To mitigate donor site morbidity, an alternative technique known as mosaicplasty has been used, in which multiple, small plugs are harvested from a portion of heathy cartilage tissue and placed into small to medium-sized defect sites. 22 The use of the patient’s own tissue and further damage to the knee joint is not ideal and further necessitates alternative strategies for defect repair. Figure 1 depicts the current treatment methods for cartilage defect repair.…”
Section: Cell Therapies For Cartilage Regenerationmentioning
confidence: 99%
“… 82 , 83 These cells have demonstrated increased interest as a potential stem cell source for cartilage regeneration due to their ease of accessibility, increased proliferative potential, and anti-inflammatory traits. 22 The isolation of ADSCs is minimally invasive and cells are easily isolated from subcutaneous fat. 84 Additionally, ADSCs have low immunogenic reactivity due to the limited expression of immunogenic antigens such as CD40, CD40L, CD80, and CD86.…”
Section: Cell Therapies For Cartilage Regenerationmentioning
confidence: 99%
“…In the context of matrix-assisted cartilage implantation (MACI), a study with a follow-up ranging from five to 12 years revealed failure rates of 18.2% and 87.5% in complex and salvage cases, respectively [ 50 ]. Autologous chondrocyte transplantation (ACT) exhibited encouraging results, with a study reporting consistent indications of cartilage regeneration over a seven-year follow-up period [ 51 ]. Examining intra-articular sprifermin in patients with knee osteoarthritis, a five-year follow-up study demonstrated the sustained structural modification of articular cartilage with sprifermin compared to a placebo over a 3.5 to four-year post-treatment period [ 52 ].…”
Section: Reviewmentioning
confidence: 99%
“…These comprehensive long-term follow-up studies collectively underscore the potential of cartilage-based procedures in providing enduring benefits in structural improvements and symptomatic relief for patients with various forms of joint disease. Nevertheless, the importance of continued long-term follow-up studies cannot be overstated, ensuring a comprehensive understanding of these procedures' enduring effectiveness and safety [ 51 ].…”
Section: Reviewmentioning
confidence: 99%